2017
DOI: 10.1596/978-1-4648-0819-7
|View full text |Cite
|
Sign up to set email alerts
|

Mining in Africa: Are Local Communities Better Off?

Abstract: This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent, or the Agence Française de Développement. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…Chuhan-Pole at al. [11], in a recent literature review, identified three main channels through which the abundance of mineral resources affects local areas. First, the market mechanism refers to the impact on demand for jobs or other local inputs and their multiplier effect on nonmining sectors through backward and forward linkages or other spillovers.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Chuhan-Pole at al. [11], in a recent literature review, identified three main channels through which the abundance of mineral resources affects local areas. First, the market mechanism refers to the impact on demand for jobs or other local inputs and their multiplier effect on nonmining sectors through backward and forward linkages or other spillovers.…”
Section: Related Literaturementioning
confidence: 99%
“…Empirical research has made greater progress in the study of the three channels, but there is still less of an advance in our understanding of how the environmental and channels interact with each other. Indeed, many studies have investigated a large spectrum of the local socioeconomic impact of the mining sector: local economic growth, agglomeration economies, demand shock, and multiplier effects on other sectors [11,[33][34][35][36], local output and employment composition ( [11,37]), local corruption and violence ( [38][39][40][41]), living standards, poverty, and inequality, [11,35,[42][43][44], and local public spending and services [45]. At the same time, a literature stream on the impact of mining on the local environment is emerging.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research on mining and development has typically focused on three areas: the impact of mining on governance, national economics and growth (e.g., [3,[6][7][8]); the relationship between mining and community-level social, economic and environmental change (e.g., [9][10][11]); and the development of socioeconomic indicators measuring mining impacts (e.g., [12][13][14]). However, over the past two decades or so, there has been an increasing focus amongst mining companies and governments concerning the notion of a "social licence to operate" (SLO) and corporate social responsibility (CSR) in response to impacts on local communities in developing nations.…”
Section: Introductionmentioning
confidence: 99%
“…While early research in mining and development, particularly on CSR, focused on African and Latin American communities (e.g., [8,17,18]), over the past several decades the approach has also become increasingly common in South East Asia (e.g., [19,20]). While the discourse of CSR has become increasingly common within South East Asia, there has been relatively little research on the subject, particularly in Vietnam (e.g., [15,21,22]) despite the nation having a long history of resource extraction.…”
Section: Introductionmentioning
confidence: 99%